Japanese political economy revisited: diverse corporate change, institutional transformation, and Abenomics. Issue 3 (3rd July 2017) - Chiavacci, David; Lechevalier, Sébastien
Abstract: This introductory article to the special issue on "Japanese Political Economy Revisited: Diverse Corporate Change, Institutional Transformation, and Abenomics" starts with a short summaryof the changing perceptions of Japan's political economy from its meteoric rise as worldwide leading model in the 1970s and 1980s to its demotiontoa problem and reform case since the later 1990s. Based on this overview, it identifies some striking issue and open questions in this conventional view of Japan's political economy as problem and the high expectations on Abenomics as Japan's current economic reform programme. Then we discuss the articles of the special issue and their new contributionsto a better understanding of the developments at the corporate level as well as institutional change and economic reforms at the macro level in the last two decades. Finally, this introductory article ends with a short outlineof a new research programme and four central research questions about the Japanese political economy.